The Person is Spiritual in the Development of Society the Place of Perfection - Mamajonov O'tkirbek Tajiddinovich (Genius Journals, 2023)
In this article, the development of society, the role and importance of the spiritual perfection of the individual in the development of society, the coherence and interdependence of the words of enlightenment and spirituality, a person's acquisition of knowledge and science and their application in daily practical activities, it is said about the development of the society based on the development of spiritual qualities such as honesty, faith, conscience, sincerity in the person
Keywords: development of society; spiritual perfection of a person